Pentingnya Pendidikan Karaker dalam Mendukung Perkembangan Moral pada Peserta Didik (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
Character education is an important aspect in supporting moral development in students. Through character education, students can be equipped with strong moral values, so that they can become individuals with good character and contribute positively to society. Character education can help students develop the ability to think critically, make the right decisions, and behave ethically. In addition, character education can also help students develop an awareness of the importance of moral values, such as honesty, empathy, and responsibility. Thus, character education is very important in supporting moral development in students and helping them become individuals with good character and contribute positively to society. Therefore, character education needs to be a priority in the education system, so that students can be equipped with strong moral values ​​and become individuals with good character.